ANALISIS PENERIMAAN DAERAH DARI INDUSTRI PARIWISATA DI PROVINSI DKI JAKARTA DAN FAKTOR-FAKTOR YANG MEMPENGARUHINYA - Arlina, Riska; Purwanti, Evi Yulia (Diponegoro Journal of Economics, 2013)
DKI Jakarta as a capital city of Indonesia has a high potential tourism to be developed. Yet, the contribution of the tourism industry to the PAD is smaller than the contribution of non tourism sector. This research aims to analyze the influence of the number of foreign and domestic tourists, investments in tourism, USD exchange rate, and the safety factor to local revenues of the tourism industry in Jakarta. This research used multiple linear regression (OLS), in 1991-2012. Type of data used is secondary data obtained from Badan Pusat Statistik (BPS) Provinsi DKI Jakarta, Department of Tourism and Culture Jakarta Capital City Government, Indonesia Investment Coordinating Board and other literature such as books and economic journals. The result of regression analysis showed that the variable number of foreign and domestic tourists and USD exchange rate influence significantly to local revenues of the tourism industry in Jakarta whereas investment in tourism and safety factors variable had no significant effect. Simultaneous test result showed that overall variable number of foreign and domestic tourists, investment in tourism, USD exchange rate, and safety factor together indicate effect to local revenue of the tourism industry in Jakarta. R-square value of 0,931 which mean 93,1 percent of local revenue of the tourism variation can be explain from fourth variation of the independent variables (number of foreign and domestic tourist, investment in tourism, USD exchange rate and safety factor), whereas the remaining 6,9 percent is explained by other factor beyond the model.